Screening for diabetes in a local population of Patan, Nepal - Maharjan, Babu Raja; Shakya, PR; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: Diabetes is increasing worldwide. Earlier detection and treatment of the diabetes slowed the complications associated with diabetes. Unfortunately, 30-50% of diabetes remains undiagnosed. This study is designed to estimate the prevalence of diabetes and diabetes risk group i.e. person with impaired fasting glucose (IFG) in the Patan. Methods: We, therefore, carried out a community based cross-sectional study for the diabetes screening using fasting plasma glucose. Results: The result showed 3.3% screen-detected and overall prevalence of 16% diabetes showing alarming picture of diabetes status in the study population. It showed significant correlation between waist circumference (WC) and WaistHip Ratio (WHR) with fasting plasma glucose (FPG) and mean arterial pressure (MAP). Conclusion: It pointed out the need of health education and promotion to the patients for prevention and progression of the disease.